Development of a novel Newcastle disease virus (NDV) neutralization test based on recombinant NDV expressing enhanced green fluorescent protein. Issue 1 (December 2017) - Chumbe, Ana; Izquierdo-Lara, Ray; Calderón, Katherine; Fernández-Díaz, Manolo; Vakharia, Vikram
Abstract Background Newcastle disease is one of the most important infectious diseases of poultry, caused by Newcastle disease virus (NDV). This virus is distributed worldwide and it can cause severe economic losses in the poultry industry due to recurring outbreaks in vaccinated and unvaccinated flocks. Protection against NDV in chickens has been associated with development of humoral response. Although hemagglutination inhibition (HI) assay and ELISA do not corroborate the presence of neutralizing antibodies (nAbs); they are used to measure protection and immune response against NDV. Methods In this study, we established a system to recover a recombinant NDV (rLS1) from a cloned cDNA, which is able to accept exogenous genes in desired positions. An enhanced green fluorescent protein (eGFP) gene was engineered in the first position of the NDV genome and we generated a recombinant NDV carrying eGFP. This NDV- eGFP reporter virus was used to develop an eGFP-based neutralization test (eGFP-NT), in which nAbs titers were expressed as the reciprocal of the highest dilution that expressed the eGFP. Results The eGFP-NT gave conclusive results in 24 h without using any additional staining procedure. A total of 57 serum samples were assayed by conventional neutralization (NT) and eGFP-NT. Additionally, HI and a commercial ELISA kit were evaluated with the same set of samples. Although HI (R 2 = 0.816) and ELISA (R 2 = 0.791) showed substantial correlation with conventional NT, eGFP-NT showed higher correlation (R 2 = 0.994), indicating that eGFP-NT is more accurate method to quantify nAbs. Conclusions Overall, the neutralization test developed here is a simple, rapid and reliable method for quantitation of NDV specific nAbs. It is suitable for vaccine studies and diagnostics.